DARK IS THE NEW LIGHT: A PARADIGM SHIFT IN THE VISUAL NARRATIVE OF INDIAN CINEMA AND WEB SERIES - Verma, Sachin Kr.; Sonkar, Akhilendra Pratap (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Indian ancient scriptures contain a rich array of rules, instructions, daily rituals, and customs, which is particularly suitable for a diverse country with its multiculturalism and diverse beliefs. Rasa theory, a fundamental concept in Indian aesthetics that has strong connections to early Indian performing arts such as dance and theater. Contemporary dark films explore themes of violence, crime, moral ambiguity, and the darker aspects of human nature. They often aim to evoke intense and unsettling emotions in the audience. Indian audiences have shown a growing interest in films that challenge conventional storytelling and explore complex and unconventional themes. Films and web series like "Gangs of Wasseypur," "Paatal Lok," "Sacred Games," and "Asur" etc. have received critical acclaim and have been embraced by audiences for their bold narratives and portrayal of darker elements. While there is an audience that enjoys dark narratives, the appreciation of dark cinema among Indian viewers is not universal. However, it has undoubtedly gained momentum and contributed to the evolving filmmaking culture in the country. The goal of this study is to analyze & explore the visual semantics applied in web series with dark themes, aiming to understand their influence on the audience. An exploratory study examines the visual elements employed in popular Indian cinema and web series that portray dark narratives.